Species diversity, abundance, and distribution of freshwater prawns along a selected perennial stream in Ngangla Gewog, Zhemgang, Southern Bhutan - Wangda Thinley; Bashir Sabreen; Suberi Bhagat; Vadhel Agrataben; Malik Tabarak; Mohan Anand (Oceanological and Hydrobiological Studies)
The study and diversity of freshwater prawns are of great importance due to growing interest in biodiversity and its relative abundance. The present study was carried out for a selected stream divided into three different habitat types: namely, pond, run, and riffle. The study was focused on the diversity and abundance of prawns. To make it more systematic, a transect was laid upon the stream and it was divided into 30 plots with 100 m intervals. Metapenaeus rosenbergii, Penaeus japonicas, and Metapenaeus insolitus were species recorded in the pond habitat type only. The Penaeus genus was the most prominent in the study area while the genus Metapenaues was the least abundant. The diversity of freshwater prawns was found to be highest in the pond rather than the run and riffle. Documented information for prawn populations in Bhutan is sparse. Therefore, there is a wide research gap regarding prawn diversity in Bhutan. This study will help to establish a baseline data for the prawn distribution in the proposed study area. The present study will serve as a reference guide for future researchers.